2003
DOI: 10.1016/s0008-6363(02)00775-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation and inactivation of a non-selective cation conductance by local mechanical deformation of acutely isolated cardiac fibroblasts

Abstract: Compression of the isolated cardiac fibroblast caused depolarization of the membrane by activating inward currents through a non-selective cation conductance (G(ns)). Stretch hyperpolarizes the fibroblast, however, not by Ca(2+) activation of K(+)-conductance. Ion selectivity, E(rev,) and Gd(3+)-sensitivity of stretch suppressed currents suggest that stretch reduces G(ns) that is activated by compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 28 publications
1
82
0
Order By: Relevance
“…These MIPs are thought to result from compression of the fibroblast membrane during systolic contraction of the cardiac myocytes and have been implicated in the mechanoelectric feedback mechanism of the heart [9,11,12,20]. Our recent patch-clamp recordings from isolated cardiac fibroblasts demonstrated that mechanical "compression" activates a gadolinium-sensitive cation conductance in the plasma membrane of these cells [7]. Compressioninduced currents were carried by Na + , K + and Cs + ions, suggesting activation of non-selective cation channels [7].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…These MIPs are thought to result from compression of the fibroblast membrane during systolic contraction of the cardiac myocytes and have been implicated in the mechanoelectric feedback mechanism of the heart [9,11,12,20]. Our recent patch-clamp recordings from isolated cardiac fibroblasts demonstrated that mechanical "compression" activates a gadolinium-sensitive cation conductance in the plasma membrane of these cells [7]. Compressioninduced currents were carried by Na + , K + and Cs + ions, suggesting activation of non-selective cation channels [7].…”
Section: Discussionmentioning
confidence: 95%
“…Our recent patch-clamp recordings from isolated cardiac fibroblasts demonstrated that mechanical "compression" activates a gadolinium-sensitive cation conductance in the plasma membrane of these cells [7]. Compressioninduced currents were carried by Na + , K + and Cs + ions, suggesting activation of non-selective cation channels [7]. Conversely, application of physical stretch to isolated fibroblasts inhibited this conductance and hyperpolarized E m [7].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Negative pressures and longitudinal stretch of ventricular myocytes increased the open probability of nonselective cation channels, depolarizing cardiac cells, while also prolonging the action potential duration (8,41,49). Additionally, in fibroblast patch clamp experiments, mechanical compression caused depolarization by way of a nonspecific inward cation current, while mechanical stretch led to hyperpolarization (21)(22)(23).…”
mentioning
confidence: 97%
“…These action potentials are based on activation of L-type calcium channels and propagate very slowly (Ͻ0.01 m/s). 16,17 In the rat, Kamkin et al 18 demonstrated that compressing and stretching could depolarize and hyperpolarize isolated atrial fibroblasts by activating and inactivating a nonselective cation conductance. In cell cocultures, cardiomyocytes and fibroblasts can form functional gap junctions, 19,20 and recently, functional fibroblast-to-myocyte gap junctional coupling has also been demonstrated in the native rabbit sinoatrial node.…”
Section: See P 394mentioning
confidence: 99%